Plan de negocios para la creación de una empresa de importación de productos cosméticos asiáticos en la ciudad de Santa Marta (2023)
The following business proposal is focused on the creation of a business model that consists in the construction of a company specialized in the import and distribution of products brought from Asia (specifically from South Korea) located in the city of Santa Marta, taking into account that in recent years this sector has had a significant growth worldwide. With the introduction of this company to the market, it seeks to create a new consumer trend that manages to satisfy the cosmetic needs that are currently at the forefront. This document carries out a quantitative type of research, taking into account that only sales units will be measured. The instruments to be used will be of a primary and secondary nature, in order to determine the feasibility of cosmetics. At the institutional level, this research is developed following the guidelines of the research area of Organizational Management